2017
DOI: 10.1177/2397002217721077
|View full text |Cite
|
Sign up to set email alerts
|

Leader strain and follower burnout: Exploring the role of transformational leadership behaviour

Abstract: This study contributes to leadership literature by linking leader strain with followers' level of burnout while considering leaders' transformational leadership behaviour. The study provides promising insights into the field of leadership theory by shedding light on the nature of leadership under stress. The sample consisted of 294 dyads of leaders and their followers, who provided information on transformational leadership style, levels of perceived strain, and burnout via an online survey. Results show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 88 publications
2
12
0
Order By: Relevance
“…The few studies that do exist suggest a crossover effect. It has been found that leaders who are under strain exert fewer transformational leadership behaviours and that such leadership behaviours LEADING WELL: 13 could protect against follower burnout, in other words, it appears that beneficial leadership behaviours are not activated in leaders who are under strain (Diebig, Poethke, & Rowold, 2017). In the present issue, M. Nielsen, Skogstad, Gjerstad, and Einarsen (2019) found that anxious leaders exerted lower levels of transformational leadership and higher levels of laissez faire leadership over time.…”
Section: Leading Well: 11mentioning
confidence: 54%
“…The few studies that do exist suggest a crossover effect. It has been found that leaders who are under strain exert fewer transformational leadership behaviours and that such leadership behaviours LEADING WELL: 13 could protect against follower burnout, in other words, it appears that beneficial leadership behaviours are not activated in leaders who are under strain (Diebig, Poethke, & Rowold, 2017). In the present issue, M. Nielsen, Skogstad, Gjerstad, and Einarsen (2019) found that anxious leaders exerted lower levels of transformational leadership and higher levels of laissez faire leadership over time.…”
Section: Leading Well: 11mentioning
confidence: 54%
“…Especially, transformational leaders contribute to innovativeness, as they are flexible, open-minded, with strategic thinking, they motivate people and explore new ideas, which results in improved team performance and business profit (Leitão et al, 2021). The studies confirm that a leader's engagement in transformational behavior decreases employee stress and burnout (Diebig et al, 2017).…”
Section: Introductionmentioning
confidence: 73%
“…The use of a clinician/administrator or physician/nurse dyadic leadership model within hospitals is growing in popularity, with documented implementation in Germany, (Steinert et al , 2006; Diebig et al , 2017) Canada (Clausen et al , 2017; Saxena et al , 2018) and the US (Clark and Greenawald, 2013; Kim et al , 2014; O'Leary et al , 2017). The articles reviewed through our search provide qualitative and quantitative assessments of the dyadic leadership model's implementation in a healthcare setting.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in traditional hospital or health system leadership models, physicians may lack authority and/or responsibility in decisions pertaining to how care delivery is structured, thus limiting their influence at a systems level (Oostra, 2016). Some attribute such lack of involvement as one important component contributing to lack of physician engagement (Zismer and Brueggemann 2010) and even burnout (Diebig et al , 2017). In response, a recent trend in clinical leadership models involves a dyadic approach at the unit level, in which the microsystem is led jointly by two individuals in different health professions with shared responsibilities and aligned goals (Zismer and Brueggemann, 2010).…”
Section: Introductionmentioning
confidence: 99%